2020
DOI: 10.2196/15973
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Self-Harm and Suicide Contagion Effects of the Blue Whale Challenge on YouTube and Twitter: Qualitative Study

Abstract: Background Research suggests that direct exposure to suicidal behaviors and acts of self-harm through social media may increase suicidality through imitation and modeling, particularly in more vulnerable populations. One example of a social media phenomenon that demonstrates how self-harming behavior could potentially be propagated is the blue whale challenge. Objective This paper aimed to investigate the way individuals portray the blue whale challenge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 80 publications
(99 reference statements)
0
27
0
5
Order By: Relevance
“…Researchers emphasize the fact that these types of videos have a negative impact on vulnerable populations by means of the socially viral effects, which occur when self-harming behavior is modeled and positioned as acceptable through video content. These effects are called suicidal infection, which teenagers and young adults are most susceptible to, especially when they see others using this behavior to achieve an attractive goal, such as attracting the attention of others (Khasawneh et al, 2020). Such practices are international in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers emphasize the fact that these types of videos have a negative impact on vulnerable populations by means of the socially viral effects, which occur when self-harming behavior is modeled and positioned as acceptable through video content. These effects are called suicidal infection, which teenagers and young adults are most susceptible to, especially when they see others using this behavior to achieve an attractive goal, such as attracting the attention of others (Khasawneh et al, 2020). Such practices are international in nature.…”
Section: Resultsmentioning
confidence: 99%
“…As young people frequently create their own content, guidance to increase safe and responsible depiction of suicide and self-harm image and video-based content are now needed to educate young people as well as media professionals. Recent analysis of videos related to the Blue Whale Challenge on YouTube has demonstrated that although these user-generated videos seek to raise awareness, most videos violate guidance around safe and effective messaging, further underscoring the need to educate social media users and content generators on safe content creation and the factors that may have either positive or negative impacts on vulnerable viewers [ 56 ]. Individuals have reported an awareness of the potential impacts of self-harm images and videos and as a consequence add trigger warnings to their own posts [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…No jogo, o sujeito era desafiado a cometer atos de automutilação e a publicar para os demais participantes. Uma vez dentro do jogo, era proibida a desistência e a última fase do jogo era o suicídio (Khasawneh et al, 2020).…”
Section: Internet E O Contágio Socialunclassified